Effect of microbiologically influence corrosion of dissimilar welded joint by pseudomonas aeruginosa - Mamat, Mohd Fauzi; Hamzah, Esah; Ibrahim, Zaharah; Abdul Majid, Rohah (Universiti Putra Malaysia, 2022)
Microbiologically influenced corrosion (MIC) is a type of destructive corrosion that can be initiated, facilitated, or accelerated by the presence of bacteria. The study aims to assess the MIC behavior of dissimilar welded joint substrates exposed to the existence of the Pseudomonas aeruginosa inoculated nutrient-rich simulated sea water medium (NRSS). The formation of the biofilm layer, corrosion precipitates and pits on the dissimilar welded substrate is studied using field emission scanning electron microscopy (FESEM), X-ray diffraction, energy dispersive spectroscopy (EDS), weight loss, and corrosion rate methods. The corrosion rate of a welded coupon immersed in a bacteria-inoculated medium was higher than that of a sterile NRSS medium. The FESEM results revealed an aggressive role for pseudomonas aeruginosa biofilm and bacteria colonisation in inducing corrosion and producing significant pits on welded joints in the HAZarea. This study may contribute to a better understanding of the MIC behavior of dissimilar welded joints caused by bacterial colonisation and biofilmformation